Determination of Training Needs of the Administrative Personnel of the Area of Economic Sciences and Management of the UNMSM - Ugarte Casafranca, Walter Davis (2020)
We present the progress of the training process of the administrative staff of the faculties of the area of ​​economic sciences and of the management of the UNMSM in the framework of the implementation of the Civil Service Law (SERVIR). Interviews have been conducted with the officials in charge of administrative management and a questionnaire has been applied to administrative staff to determine training needs. Likewise, the job profiles and personal profiles for the administration positions of the aforementioned faculties have been studied. The most outstanding result is that emphasis should be placed on the development of soft skills. These include teamwork and conflict resolution. We have also found that, due to the constant turnover of staff and low salaries, there is less qualified personnel, which is more noticeable in the case of hired personnel. Regarding the implementation of the Civil Service Law, the faculties studied have not implemented any plans or budget for the training of their administrative staff, which jeopardizes the quality of the service they provide. Although it is true that UNMSM is in the process of improvement, training of personnel must be reinforced since in this area and in the application of the Civil Service Law (SERVIR) we are still behind.